Three Design Basis Accidents’ Analysis on the HTR-10GT - Minggang Lang; Heng Xie; Yujie Dong (Science and Technology of Nuclear Installations)
The study simulated the design basis accidents (DBAs) sequences of the HTR-10GT core with THERMIX. When a DBA happens, the protection system will receive a scram signal which shall lead to active measures to shut down the reactor following it. In the paper, three typical DBA cases were studied. They include an accident induced by station blackout, a case caused by the withdrawal of one control rod out of the core by a mistake, and a case resulting from an earthquake, respectively. The simulation results illustrate that the fuel peak temperatures in the core during these accidents are 1066°C, 1201°C and 1067°C, respectively. It is shown that the HTR-10GT has a good safety characteristic.